Complexities of Legislative Representation in Ghana: Do Legislators Really Represent Their Constituents? - Agomor, Kingsley S.; Djietror, Ebenezer Ahumah (Journal of Legal Studies, 2025)
The question of whose interest legislators really represent is yet to be satisfactorily answered in the literature of legislative studies. The paper investigates whether Members of Parliament (MPs) in Ghana follow their constituents’ preference, their own judgment, or their parties’ interests. Qualitative data was collected through 25 in-depth interviews with MPs, senior parliamentary staff, Parliamentary press corps, and civil society groups. Using theoretical literature on ideal styles of representation—delegate, partisan, and trustee— the delegate role of MPs in relation to their constituents was largely overshadowed by the delivery of personalized and club goods as a way of representing their constituents. However, on a matter of policy, a partisan orientation strongly influences the legislative decision-making of MPs. This is due to the economic leverage that political parties have over their candidates’ re-election bid and a whip system that can compel MPs to prioritize the party’s interest over that of constituents and their own judgment. Informal factors, such as ethnicity, religion, schoolmates, family relations, and friendship, though they play a minor role in influencing their representational orientation, could potentially shape the secret dissenting views of MPs from their parties’ positions. These findings highlight the need to enhance public education on the core responsibilities of MPs. This will foster an enduring trustee relationship, essential for reducing excessive pressure and demands on MPs, and undue partisanship in legislative policy-making.